Bioactive pentacyclic triterpenoids from the whole plants of Pterocephalus hookeri. (March 2022) - Zhang, Jun-Sheng; Qian, Yong; Xin, Zhen-Qiang; Cao, Xin-Xin; Yang, Zhou; Zhang, Hua
Abstract: Eight undescribed triterpenoids (pterohoonoids A−H) including four oleananes, one nor-oleanane and three nor-ursanes, along with seven known analogues, were isolated from the whole plants of Pterocephalus hookeri (Dipsacaceae). The structures with relative stereochemistries of these molecules were elucidated mainly by spectroscopic analyses, and the absolute configurations of the undescribed ones were assigned by a variety of methods, including time-dependent density functional theory (TD-DFT) based electronic circular dichroism (ECD) calculation, Rh2 (OCOCF3 )4 -induced ECD experiment and chemical transformation. The inhibitory effects toward the diabetes target α -glucosidase of all the isolates were assessed, and four of them exhibited pronounced activity with IC50 values ranging from 6.8 to 55.8 μ M. In addition, four compounds also showed inhibition against the nitric oxide (NO) production induced by lipopolysaccharide (LPS) in RAW264.7 macrophage cells (IC50 = 12.4–63.7 μ M). Further assays demonstrated that the most active compound pterohoonoid A inhibited the release of two key pro-inflammatory cytokines TNF- α and IL-6 in a dose-dependent manner. Graphical abstract: Image 1 Highlights: Eight undescribed triterpenoids were isolated from Pterocephalus hookeri. The absolute configurations of the compounds were determined by extensive methods. Four compounds exhibited pronounced inhibitory activity against α-glucosidase. Four compounds exhibited inhibition against the nitric oxide production. The inhibitory effects on pro-inflammatory factors TNF-α and IL-6 were investigated.